Strictures in Crohn's disease are characterised by an accumulation of mast cells colocalised with laminin but not with fibronectin or vitronectin. (1st August 1999) - Gelbmann, C M; Mestermann, S; Gross, V; Köllinger, M; Schölmerich, J; Falk, W
Abstract : BACKGROUND/AIMS: Intestinal fibrosis and stricture formation is an unresolved problem in Crohn's disease. The aim of this study was to investigate whether mast cells accumulate in these tissues and whether their localisation is associated with extracellular matrix components. METHODS: Mast cells were visualised by immunohistochemical staining of the mast cell specific proteases chymase and tryptase. Their localisation in relation to extracellular matrix components was shown by immunohistochemical double labelling. RESULTS: In strictures in Crohn's disease, a striking accumulation of mast cells was seen particularly in the hypertrophied and fibrotic muscularis propria, with a mean (SEM) mast cell number of 81.3 (14.9) v 1.5 (0.9)/mm 2 in normal bowel (p<0.0005). All mast cells in the muscularis propria were colocalised with patches of laminin. In contrast, in the submucosa, laminin was exclusively found in the basal lamina of blood vessels where many adherent mast cells were seen. No colocalisation of mast cells was found with fibronectin or vitronectin. CONCLUSIONS: The large accumulation of mast cells in the muscle layer of strictured bowel suggests a functional role for these cells in the hypertrophic and fibrotic response of the smooth muscle cells. The colocalisation with laminin indicates a mechanism of interaction between smooth muscle cells and mast cells that may be important in the role of mast cells in the process of fibrosis.